A Real-Business-Cycle model with endogenous discounting and a government sector - Aleksandar Vasilev (ZBW – Leibniz Information Centre for Economics, 2018)
We introduce an endogenous discount factor as in Uzawa (1968) and Schmitt-Grohe and Uribe (2003) into a real-business-cycle setup with Greenwood et al. (1988) preferences and augment the model with a detailed government sector. We calibrate the arti ficial economy to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of endogenous discounting for the propagation cyclical fluctuations in Bulgaria. The presence of an endogenous discount factor improves the model performance against data, and in addition this extended setup dominates the standard RBC model framework with a constant discount factor, e.g., Vasilev (2009).
Keywords: 330; Business cycles; Uzawa preferences; endogenous discounting; Bulgaria